CORRELATION ANALYSIS OF IMMUNOLOGICAL MARKERS IN CHILDREN WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Faizullaeva N.Ya.; Ashurova D. T.; Shermatova Z. A.; Raufov A. A. (Modern American Journals, 2025)
The study included 97 children aged 7–17 years with a confirmed diagnosis of systemic lupus erythematosus. A correlation analysis of immunological markers was performed, including CRP, lactoferrin, IFNγ, IP-10, C3, C4, and CD16⁺ cells. Strong significant negative correlations were found between CRP and lactoferrin (r = –0.83; p < 0.001), CRP and IFNγ (r = –0.79; p < 0.001), as well as a positive correlation between CRP and CD16⁺ cells (r = 0.82; p < 0.001). Lactoferrin was positively correlated with IFNγ (r = 0.80; p < 0.001) and IP-10 (r = 0.76; p < 0.001), indicating a coupled activation of the innate immune response. Moderate correlation was established between complement components C3 and C4 (r = 0.58; p < 0.01), and weak associations between IP-10 and C4 (r = –0.44; p < 0.05) indicate a complex regulation of inflammation. The results emphasize the importance of CRP, lactoferrin, IFNγ, IP-10 and CD16⁺ markers in the pathogenesis of SLE in children and can be used to assess disease activity.
Keywords: Systemic lupus erythematosus; children; immunological markers; C-reactive protein; interferon-gamma; IP-10; lactoferrin; CD16⁺; complement; correlation analysis.